Price Fairness, Waiting Time, And Patient-Doctor Communication In Influencing Patient Satisfaction And Revisit Intention At Xyz Primary Clinic, Bandung City: SEM-PLS And IPMA - Putu Ratih Wijayanthi; Innocentius Bernarto (Dinasti International Journal of Education Management And Social Science, 2025)
In the past two years, the flow of general patients at XYZ Primary Clinic located in Bandung City has decreased. This happened without any modification to the service protocol. The purpose of this study was to determine how price fairness, waiting time, doctor-patient interaction, and patient satisfaction affect intention to return and overall satisfaction with the clinic. These three service-defining non-medical factors are considered to be very important for measuring service quality. SEM-PLS and IPMA were used for this study in quantitative form. A validated questionnaire was administered to 177 patients of XYZ Primary Clinic in Bandung City, which resulted in data collection. Based on the analysis, it was found that price fairness and doctor-patient communication significantly increased satisfaction; however, waiting time had a negative impact on satisfaction. In addition, patient satisfaction increases the intention to revisit the clinic. Furthermore, the results show that satisfaction can strengthen the influence of these three independent variables on return intentions. Through the use of IPMA, findings revealed that doctor-patient communication performed below expectations, yet was the most influential, making this aspect a focal point for improvement. This analysis highlights the need to improve communication among medical staff, sharpen operational service workflows, and make pricing transparent to encourage greater patient loyalty. The conclusions drawn from this analysis can strategically guide clinic administrators on policy decisions aimed at improving service quality from a patient perspective.